Cu2+-Citrate Dimer Complexes in Aqueous Solutions - Yahia Z. Hamada,; Robin Cox ,; Hasan Hamada, (Journal of Basic & Applied Sciences, 2015)
The UV-Vis spectra, speciation diagrams, and potentiometric profiles for Cu2+-citrate complexesin aqueous solutions are presented. As the pH increases from 2.29 to 5.15, the UV-Vis spectral profile of the Cu2+-citrate complexes showed a blue shift from 820 nm to 760 nm. We have set the conditions to construct the speciation diagram as follow: Cu2+:citric acid was in 1:1 ratio with concentration of 1.0 x 10-4 mol.L-1, 0.1023 mol.L-1 NaOH solution, and pKw = 13.781 ± 0.006 taken from Sweeton, Mesmer, and Baes. The current report is the first potentiometric study that has taken into accounts two Cu-Cit dimeric species to be refined simultaneously. These spectroscopic and potentiometric data are discussed which augment what had been reported in the literature.